Speech Auditory Brainstem Responses: Effects of Background, Stimulus Duration, Consonant–Vowel, and Number of Epochs. Issue 3 (May 2019) - BinKhamis, Ghada; Léger, Agnès; Bell, Steven L.; Prendergast, Garreth; O'Driscoll, Martin; Kluk, Karolina
Abstract : Objectives: The aims of this study were to systematically explore the effects of stimulus duration, background (quiet versus noise), and three consonant–vowels on speech-auditory brainstem responses (ABRs). Additionally, the minimum number of epochs required to record speech-ABRs with clearly identifiable waveform components was assessed. The purpose was to evaluate whether shorter duration stimuli could be reliably used to record speech-ABRs both in quiet and in background noise to the three consonant–vowels, as opposed to longer duration stimuli that are commonly used in the literature. Shorter duration stimuli and a smaller number of epochs would require shorter test sessions and thus encourage the transition of the speech-ABR from research to clinical practice. Design: Speech-ABRs in response to 40 msec [da], 50 msec [ba] [da] [ga], and 170 msec [ba] [da] [ga] stimuli were collected from 12 normal-hearing adults with confirmed normal click-ABRs. Monaural (right-ear) speech-ABRs were recorded to all stimuli in quiet and to 40 msec [da], 50 msec [ba] [da] [ga], and 170 msec [da] in a background of two-talker babble at +10 dB signal to noise ratio using a 2-channel electrode montage (Cz-Active, A1 and A2-reference, Fz-ground). Twelve thousand epochs (6000 per polarity) were collected for each stimulus and background from all participants. Latencies and amplitudes of speech-ABR peaks (V, A, D, E, F, O) were compared across backgrounds (quiet and noise) for all stimulus durations, across stimulus durations (50 and 170 msec) and across consonant–vowels ([ba], [da], and [ga]). Additionally, degree of phase locking to the stimulus fundamental frequency (in quiet versus noise) was evaluated for the frequency following response in speech-ABRs to the 170 msec [da]. Finally, the number of epochs required for a robust response was evaluated using F sp statistic and bootstrap analysis at different epoch iterations. Results: Background effect: the addition of background noise resulted in speech-ABRs with longer peak latencies and smaller peak amplitudes compared with speech-ABRs in quiet, irrespective of stimulus duration. However, there was no effect of background noise on the degree of phase locking of the frequency following response to the stimulus fundamental frequency in speech-ABRs to the 170 msec [da]. Duration effect: speech-ABR peak latencies and amplitudes did not differ in response to the 50 and 170 msec stimuli. Consonant–vowel effect: different consonant–vowels did not have an effect on speech-ABR peak latencies regardless of stimulus duration. Number of epochs: a larger number of epochs was required to record speech-ABRs in noise compared with in quiet, and a smaller number of epochs was required to record speech-ABRs to the 40 msec [da] compared with the 170 msec [da]. Conclusions: This is the first study that systematically investigated the clinical feasibility of speech-ABRs in terms of stimulus duration, background noise, and number of epochs. Speech-ABRs can be reliably recorded to the 40 msec [da] without compromising response quality even when presented in background noise. Because fewer epochs were needed for the 40 msec [da], this would be the optimal stimulus for clinical use. Finally, given that there was no effect of consonant–vowel on speech-ABR peak latencies, there is no evidence that speech-ABRs are suitable for assessing auditory discrimination of the stimuli used. Abstract : Supplemental Digital Content is available in the text.